The needs to develop a positive student discipline model through the assessment of the project for strengthening the student’s profile of Pancasila - Desniwati, Desniwati; Sari, Vivi Puspita; Fitria, Riana Agus (Research in Education and Technology (REGY), 2024)
It is important to develop positive discipline through assessment of the project for strengthening the student’s profile of Pancasila (P5) so that students can form their character indirectly. The values of the P5, namely 1) have faith, be devoted to God Almighty, and have a noble character, 2) be independent, 3) work together, 4) global diversity, 5) critical reasoning, and 6) creative. This research aimed to describe developing a positive discipline model by assessing the project to strengthen the P5. The development of this positive discipline was through an assessment of the project to strengthen the P5 among students, especially phase E students at SMAN 1 Pulau Punjung so that they can form positive character. The research method was carried out using non-associative quantitative analysis with a sample of 73 students from a population of 268. Based on the needs analysis distributed through a questionnaire, it can be concluded that the development of a positive discipline model was needed according to the interest indicator reaching 90% in the very high category. Meanwhile, the needs indicator reached 89% in the high category.